Higher moments in the fundamental specification of electricity forward prices. Issue 11 (2nd November 2022) - Gianfreda, Angelica; Scandolo, Giacomo; Bunn, Derek W.
Abstract : An extended specification for estimating the risk premia necessary for the forward pricing of wholesale electricity is developed in order to respond to the increasing need for more precise risk management of hedging positions in practice. Using Taylor expansions, we provide new specifications for the electricity forward premium including its dependency on all four moments of the expected wholesale price density as well as the higher moments of the demand density including skewness and kurtosis. Overall we argue that previous models have been underspecified and that the extended formulation proposed in this analysis is robust and worthwhile.